(untitled) (International Journal of Engineering and Computer Science, 2014)
Mobile adhoc network (MANETs) is emerging wireless technology for research field that work with reactive,proactive and hybrid routing protocols. In MANETs , mobility is major issues on mobile adhoc networks, there are several problems in routing with Mobile Ad hoc Networks like asymmetric links ,routing overhead , dynamic topology and interference.This paperfocused on ZRP to designing scenario for parameters that give its best and how much effective this protocol is.NS-2.34 simulator environment has been used to analysis the performance of ZRP for different zone radius by varying mobility rate and communication distance along with zone radius on QoS based performance metrics.